2013
DOI: 10.1371/journal.pmed.1001393
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Age-Related Macular Degeneration in Nakuru, Kenya: A Cross-Sectional Population-Based Study

Abstract: Using digital retinal photography and slit lamp examination in a population-based sample in the Nakuru District of Kenya, Andrew Bastawrous and colleagues determined the prevalence of age-related macular degeneration in adults 50 years and older.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 41 publications
0
20
1
Order By: Relevance
“…[15] Early and late AMD prevalence were 11.2% and 1.2%, respectively. [9] The proportion of overall ARMD was 1.38% .The proportion of agerelated maculopathy (ARM) and late ARMD was 1.14% and 0.24% respectively. [6] The prevalence of ARMD in our study was 7.20%.The difference between our study and the previous studies may be due to the difference in classification of ARMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15] Early and late AMD prevalence were 11.2% and 1.2%, respectively. [9] The proportion of overall ARMD was 1.38% .The proportion of agerelated maculopathy (ARM) and late ARMD was 1.14% and 0.24% respectively. [6] The prevalence of ARMD in our study was 7.20%.The difference between our study and the previous studies may be due to the difference in classification of ARMD.…”
Section: Discussionmentioning
confidence: 99%
“…It has remained an important cause of blindness globally since the last World Health Organization survey in 2002, in which it was identified as the leading cause of blindness in high-income countries. [9] In this retro/prospective study of retinal diseases, we determined the pattern of Macular Disorders among the patients who reported for photographic evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Early and late AMD prevalence in adults aged 50 years and above was 11.2% and 1.2%, respectively, amongst participants graded on digital retinal images (n = 3,304). After controlling for age, women had a higher prevalence of early AMD than men (odds ratio 1.5; 95% CI, 1.2-1.9), and the overall prevalence rose significantly with each decade of age (Mathenge et al 2013).…”
Section: Age-related Macular Degeneration In Africamentioning
confidence: 97%
“…Comparative data between Caucasians and Africans living in the same geographical area have suggested differing predispositions towards AMD (Sommer et al 1991). A single population-based study based in SSA (Kenya) determining the prevalence of AMD was identified (Mathenge et al 2013). Early and late AMD prevalence in adults aged 50 years and above was 11.2% and 1.2%, respectively, amongst participants graded on digital retinal images (n = 3,304).…”
Section: Age-related Macular Degeneration In Africamentioning
confidence: 99%
“…While most epidemiological studies conducted before 2000 targeted populations of European descent living in industrialized countries (North America, Europe, and Australia) [3,4,5,6,7], more recent studies have been conducted in minorities of the US population (African Americans, Hispanics, and Asians) [8,9,10,11], as well as in Asia (Japan, China, India, and Singapore) [12]. However, very little is known of the epidemiology of AMD on the African continent [13]. …”
Section: Introductionmentioning
confidence: 99%